Exploration of EDTA sodium salt as novel draw solution in forward osmosis process for dewatering of high nutrient sludge - Nguyen Thi Hau (2023)
In this study, a hybrid forward osmosis–nanofiltration (FO/NF) process was designed for dewatering high nutrient containing sludge and recovering draw solution with minimum energy as well as low fouling. A novel draw solution – EDTA sodium salt – was also systematically studied for dewatering process. Results show that using EDTA sodium salt produced higher water flux and lower reverse salt flux when compared to conventional inorganic salt (NaCl) at pH 8. The final sludge concentration reached 32,000mg/L after 16h of operation. Moreover, nutrient compounds in sludge were successfully removed by the FO membrane with a removal efficiency of approximately 97% of NH4+–N, 90% of NO3−–N, 97% of NO2−–N and 99% of PO43−–P, which was attributed to the multi-barrier layers of sludge forming on membrane surface and the steric effect of the FO membrane. The NF recovery of EDTA sodium salt indicated that all NF membranes performed well and TS-80 was the best among the tested membranes.